2005
DOI: 10.1007/s11055-005-0095-0
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic Preconditioning of the Rat Brain as a Method of Endothelial Protection from Ischemic/Repercussion Injury

Abstract: The studies reported here addressed the endothelium-protecting action of local and remote ischemic preconditioning of the brain in rats. Cerebral ischemia lasting 30 min was reproduced by thermocoagulation of the vertebral arteries with simultaneous clamping of the carotid arteries, the procedure being followed by reperfusion via the carotid arteries for 120 min (controls). The early and late phases of ischemic preconditioning and remote preconditioning were reproduced. Brain blood flow was recorded using high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 12 publications
2
34
0
3
Order By: Relevance
“…The early and late phases of local IPC and the late phase of remote IPC were found to have endothelium-protecting actions evidenced as improvements in the recovery of cerebral blood flow in the postischemic period in preconditioned rats, with lower levels of endothelial desquamation and cerebral edema (Vlasov et al, 2005). Preconditioning with lipopolysaccharide (LPS), as a preconditioning stimulus, prevented ischemic cell death by reducing lesion size, and reduction of local cerebral blood flow in the peri-infarct area was inhibited in the LPS group, which was correlated with eNOS expression (Furuya et al, 2005).…”
Section: Ischemia and Inducible Nitric-oxide Synthasementioning
confidence: 96%
“…The early and late phases of local IPC and the late phase of remote IPC were found to have endothelium-protecting actions evidenced as improvements in the recovery of cerebral blood flow in the postischemic period in preconditioned rats, with lower levels of endothelial desquamation and cerebral edema (Vlasov et al, 2005). Preconditioning with lipopolysaccharide (LPS), as a preconditioning stimulus, prevented ischemic cell death by reducing lesion size, and reduction of local cerebral blood flow in the peri-infarct area was inhibited in the LPS group, which was correlated with eNOS expression (Furuya et al, 2005).…”
Section: Ischemia and Inducible Nitric-oxide Synthasementioning
confidence: 96%
“…IVC). Ischemic preconditioning in rats improved CBF during the reperfusion that followed the subsequent 30-min forebrain ischemia, and this functional effect was associated with reduced endothelial desquamation and brain edema (426). An upregulation of endothelial NOS (eNOS) may also contribute to improved recirculation in tolerant brain regions, since increased expression of eNOS mRNA was associated with ischemic tolerance induced by ischemic or LPS preconditioning (127,152,127).…”
Section: Does Preservation Of the Vascular Reactivity After The Testmentioning
confidence: 99%
“…Transient ischemia and reperfusion of limbs can elicit RIPC. Experimental animal studies have shown that RIPC reduces the volume of cerebral infarction caused by subsequent cerebral artery occlusion [8][9][10][11][12] . A clinical trial has also shown that RIPC could improve cerebral perfusion and could reduce recurrent strokes in patients with intracranial arterial stenosis [13] .…”
Section: Introductionmentioning
confidence: 99%